2013
DOI: 10.1107/s1600536813026585
|View full text |Cite
|
Sign up to set email alerts
|

Bis[μ-N-(pyridin-2-ylmethyl)pyridin-3-amine-κ2N:N′]disilver(I) bis(perchlorate) dimethyl sulfoxide disolvate

Abstract: In the binuclear title compound, [Ag2(C11H11N3)2](ClO4)2·2C2H6SO, the complex cation is centrosymmetric, with the unique AgI cation coordinated by two pyridine N atoms from two symmetry-related N-(pyridine-2-ylmeth­yl)pyridine-3-amine ligands in a geometry slightly distorted from linear [N—Ag—N = 170.78 (9)°], resulting in the formation of a 16-membered cyclic dimer. The two pyridine rings coordinating to the AgI atom are almost perpendicular to each other [dihedral angle = 87.73 (10)°]. Inter­molecular Ag⋯O i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The single-crystal structure analysis showed that 3 is a fascinating cyclic tetramer of formula [Ag 4 (pyim) 4 ]­·(CF 3 SO 3 ) 4 that is built up from the alternating connection of four Ag­(I) ions to four ligands. Although examples of cyclic dimers consisting of two ligands and two Ag­(I) ions, as in the case of complex 1 , are common in the literature, cyclic tetramers composed of four ligands and four silver­(I) ions are unusual. , The cyclic tetramer is located around a crystallographic inversion center. Therefore, the asymmetric unit is composed of two Ag­(I) ions (Ag1 and Ag2), two pyim ligands, and two trifluorosulfonate anions.…”
Section: Resultsmentioning
confidence: 99%
“…The single-crystal structure analysis showed that 3 is a fascinating cyclic tetramer of formula [Ag 4 (pyim) 4 ]­·(CF 3 SO 3 ) 4 that is built up from the alternating connection of four Ag­(I) ions to four ligands. Although examples of cyclic dimers consisting of two ligands and two Ag­(I) ions, as in the case of complex 1 , are common in the literature, cyclic tetramers composed of four ligands and four silver­(I) ions are unusual. , The cyclic tetramer is located around a crystallographic inversion center. Therefore, the asymmetric unit is composed of two Ag­(I) ions (Ag1 and Ag2), two pyim ligands, and two trifluorosulfonate anions.…”
Section: Resultsmentioning
confidence: 99%